(3EjVGM GdefgL aj GdLeY Hjf cJGHj GdJfHjg hGdeHgL dGHf Lfjs - (3CHh ESMGb EHQGgje Hf eMeO Hf edchf GdMVQejs; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3bGd GHQGgje gPG cJGH LeYJ ajg Hjf cJGHi CHj GdaJM YKeGf Hf Lfi GdPjf cGf hVYgeG Ydi MeGSI CHj JeGe MHjH Hf ChS hSej CHh GdaJM CMO gPjf GdcJGHjf GdefgL Vefg JaSjQ eG Cecfg ef CSeGA TYQGA GdMeGSI, s
(3BNQgG (B:s
(3ced HGH GdMeGSI, hGdMeO ddg cKjQkG hUdi Gddg Ydi SjOfG hfHjfG eMeO hYdi Bdg hUMHg hSde JSdjeG s
(3HgG ebGHdI ef GdbQf GdKGef GdgLQis
(3bGe HLeYg OjhGfkG hGMOkG dJcJed Hg GdaGFOI YHOGdegjef Hf eMeO Hf YHOGdegjef GdMVQejs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs